Implementasi Layanan Dukungan Psikososial Melalui Terapi Bermain dan Phbs Terhadap Anak Pasca Bencana Erupsi Gunung Semeru di Desa Sumber Mujur, Kabupaten Lumajang, Jawa Timur: Implementation of Psychosocial Support Services Through Play Therapy and Phbs for Children Post the Mount Semeru Eruption Disaster in Sumber Mujur Village, Lumajang District, East Java - Aini, Nur; Esterilita, Mari; Hanafi Rochman, Uut (J.Abdimas: Community Health, 2024)
Disasters such as the eruption of the merapi mountain are a natural event that can interfere and threaten human life like the erupting of Mount Semeru. Children are the successor generation of the nation, psychological trauma will impede the child's ability to grow and develop well in the psychological and physical aspects. A form of intervention that can be performed is the psychosocial support service (LDP), the LDP aims to improve the social functioning of children through play therapy and provide understanding of clean and healthy living behavior (PHBS) in children after disasters. The PLA method is used as a participatory approach to helping children victims of disasters in LDP activities, by involving the learning process of groups in an interactive manner, the target in this activity is 29 children who became victims after the eruption of the mountain semeru. The techniques used are interviews and observations. This dedication consists of four stages: planning, preparation, implementation, and evaluation. The results of this dedication showed that children involved in LDP experienced an improvement in problem-solving skills, such as children being able to express emotions, collaborate with others, and show greater empathy besides children applying a clean and healthy post-disaster lifestyle (PHBS). They showed increased awareness and compliance with health practices, such as washing hands andining dental hygiene. These children also act as agents of change in their communities by educating others about the importance of PHBS.